MSMEs IN TIME OF COVID-19 PANDEMIC. STRATEGY AND CHALLENGES OF ECOMMERCE ADOPTION: EVIDENCE FROM INDONESIA (The Indonesian Journal of Business Administration, 2021)
MSME in both developing and developed countries play an important role in industrialization and economic growth by contributing significantly to increasing the workforce, increasing income and catalyzing growth in both cities and villages. E-commerce technology is now generally accepted, and its use can provide numerous benefits to companies, especially small and medium-sized enterprises. Big corporations, on the other hand, are largely responsible for the expansion in e-commerce use by enterprises. As opposed to bigger corporations, MSME acceptance of e-commerce lags behind. Furthermore, MSME in developed countries continue to struggle to implement e-commerce technologies into their operations. Obstacles such as a lack of human resources, internal opposition, and unprepared customers and corporate associates, to name a few. lack of support, security issues and high cost still preventing MSME to adopt e-commerce technology. In order to formulate strategies for MSME, Comprehensive strategy-formulation framework is chosen. According to analysis, the priority order of strategies for MSME to adopt e-commerce technology are government intervention followed by partnership, training school and communication leadership. Keywords: E-Commerce, MSMEs, Barriers, Strategy